Sexual Dysfunction Improvement after Kidney Transplantation: A Prospective Study in Men and Women. Issue 1 (2nd January 2021) - Laguerre, Mélanie; Bouvier, Nicolas; Guleryuz, Kerem; Doerfler, Arnaud; Parienti, Jean-Jacques; Ait Said, Khelifa; Tillou, Xavier
Abstract: Objectives: To assess the influence of renal transplantation on sexual function. Methods: Prospective study including all patients who underwent a kidney transplantation between January 2013 and February 2015. Sexual function was measured before, at 6, 12 months after transplantation and at the last follow-up with IIEF (International Index of Erectile Function) and FSFI (Female Sexual Function Index questionnaires). Results: Median FSFI total score significantly increased in women at 6 months. In men, median IIEF total score significantly increased at one year. Conclusion: Our study provides evidence suggesting that successful transplantation can improve normal sexual function in both men and women with chronic kidney failure.